2022
DOI: 10.3390/molecules27217329
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant, Antimicrobial, and Anti-Inflammatory Properties of Origanum compactum Benth Essential Oils from Two Regions: In Vitro and In Vivo Evidence and In Silico Molecular Investigations

Abstract: The purposes of this investigatory study were to determine the chemical composition of the essential oils (EOs) of Origanum compactum from two Moroccan regions (Boulemane and Taounate), as well as the evaluation of their biological effects. Determining EOs’ chemical composition was performed by a gas chromatography–mass spectrophotometer (GC-MS). The antioxidant activity of EOs was evaluated using free radical scavenging ability (DPPH method), fluorescence recovery after photobleaching (FRAP), and lipid peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The interest of the nutraceutical industry is focused on discovering natural compounds that possess both biological and organoleptic properties, thus introducing "smart food" that can be included in a health-promoting diet. Medicinal plants and their derivatives such as essential oils contain a wide variety of bioactive compounds that possess beneficial properties such as antioxidant and anti-inflammatory activities [31,32]. It is known that several essential oils obtained from different plants have hepatoprotective effects contrasting the pro-inflammatory, pro-oxidant, and pro-fibrotic activities of hepatotoxic molecules [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The interest of the nutraceutical industry is focused on discovering natural compounds that possess both biological and organoleptic properties, thus introducing "smart food" that can be included in a health-promoting diet. Medicinal plants and their derivatives such as essential oils contain a wide variety of bioactive compounds that possess beneficial properties such as antioxidant and anti-inflammatory activities [31,32]. It is known that several essential oils obtained from different plants have hepatoprotective effects contrasting the pro-inflammatory, pro-oxidant, and pro-fibrotic activities of hepatotoxic molecules [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The LOX-5 inhibitory activity of the EO was calculated within the range IC50 = 0.68 ± 0.02 -1.33 ± 0.01 µg/mL. Besides, EO diminished the inflammation in the mice [52]. In a previous study, Demirci et al [53] observed the potential inhibitory effect of the commercial EOs belonging to Origanum ssp.…”
Section: Enzyme Inhibitory Activitymentioning
confidence: 91%
“…Also, O. compactum essential oils sampled from Boulemane and Taounate were evaluated using the disc diffusion test, and they were very active against E. coli, B. subtilis, S. aureus, and L innocua strains. Moreover, the samples collected from Boulemane region showed the uppermost activity due to their highest composition of carvacrol, 45.80% [46].…”
Section: Disk Diffusion Testsmentioning
confidence: 98%
“…Actually, the EC50 value for OCEO was around 2.25 ± 0.11 mg/mL compared to 0.031 ± 0.001 mg/mL found for ascorbic acid (Table 2). Al Mijjali et al [46] noticed a higher antioxidant power with an EC50 of 0.19 ± 0.03 mg/mL and 0.25 ± 0.04 mg/mL for essential oils extracted from O. compactum collected from two different regions in Morocco (Boulemane and Taounate). As for TZEO, the antioxidant power was 2.16 ± 0.13 mg/mL, which was feeble compared to the ascorbic acid's antioxidant power.…”
Section: Antioxidant Capacity By Frapmentioning
confidence: 99%